2020
DOI: 10.3390/app10134670
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Slags Produced by Smelting of Metallurgical Dusts and Lateritic Ore Fines in Manufacturing of Slag Cements

Abstract: A pyrometallurgical process was developed for the recycling of Ni bearing dusts and laterite ore fines by direct reduction smelting in DC (direct current) arc furnace. In the course of the performed industrial trials, besides the Ni-recovery in the liquid bath, slag composition was deliberately adjusted in order to produce a series of metallurgical slags with different chemical and mineralogical composition. The aim of this study was to investigate their suitability as clinker substitute in cement manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…At last, it should be noted that due to the different types, composition and production methods of slag, a huge different performance of AAM can be found by using the same formula but different slags [ 53 , 54 ]. Also, the effect of polymer latex on the properties of AAM can be significantly altered.…”
Section: Discussionmentioning
confidence: 99%
“…At last, it should be noted that due to the different types, composition and production methods of slag, a huge different performance of AAM can be found by using the same formula but different slags [ 53 , 54 ]. Also, the effect of polymer latex on the properties of AAM can be significantly altered.…”
Section: Discussionmentioning
confidence: 99%
“…GBFS contains adequate amounts of aluminum, silicon, and calcium oxide, making it an appropriate precursor for producing SCGC mixtures. In GCs or mortars, using GBFS as a binder can increase the compressive strength (CS) owing to better structuring of poorly arranged microstructures, micro-filling of voids, twin creations during calcium silicate hydrate (C-S-H) gel formation, and the existence of extremely polymerized units of alkali activation [16][17][18]. Nonetheless, the large CO 2 emission and EE during the production stage along with the poor durability to H 2 SO 4 exposure and rapid setting time limit the consumption of GBFS in SCGCs.…”
Section: Introductionmentioning
confidence: 99%
“…FA incorporation lowers the levels of Ca and constitutes one of the best industrial by-products to produce alkali-activated concrete for several reasons, including its wide availability in many countries, high contents of SiO 2 and Al 2 O 3 , and low cost and energy requirements [19][20][21]. Likewise, FA-incorporated GCs give reliable flexibility to heat curing for long-term and short-term in the environment [18,22,23]. However, the main problem for the extensive application of FA in GCs is related to its reduced strength development upon curing at room temperature and the requirement for high-molarity (Up to 10 M) sodium hydroxide (NaOH, hereafter called NH) and alkaline activator solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Slag-based geopolymer (SG) is an attractive alternative to Portland cement (PC). It can reuse the industrial by-product, i.e., ground granulated blast furnace slag (GGBFS), in an efficient way using alkali activation [ 1 , 2 , 3 ]. In addition, it reduces significantly the CO 2 emissions produced during the production of PC, making it a greener solution [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it reduces significantly the CO 2 emissions produced during the production of PC, making it a greener solution [ 4 , 5 ]. The main hydration product of SG is C-S-H gel with a lower Ca/Si ratio than traditional PC and no zeolite or mica hydrations are found [ 1 , 2 , 3 ]. Extensive studies have demonstrated that SG can exhibit similar mechanical strength with or even perform better than PC does in many aspects, including low hydration heat, high early strength, good durability, and resistance to chemical attack [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%